(untitled) (Global Journal of Human-Social Science, 2022)
This publication is rather peculiar because sociological studies were only allowed to be conducted from the 1960 s in Hungary under the Socialist regime as the system finally recognized this field of science - although it was kept under surveillance Losonczi 2020 This period clearly left a mark on the study however the author cleverly integrated the mandatory steps and only makes this work more authentic